O ensino da contabilidade gerencial nos cursos de graduação em Ciências Contábeis no estado de Minas Gerais, na ótica dos profissionais da Contabilidade - Anselmo Ferreira Duca (2011)
Higher education aims primordially to prepare individuals for the labor market, providing them with sufficient knowledge to professional life. This discussion although necessary have generated few studies in the nationwide and even fewer yet when it is related to the formation of the counter to operate in the Management Accounting area. This area has among its objectives to promote the knowledge and businessorganizations in which they operate, as well as to allow the control and planning of actions and provide consistent decision-making within the good management parameters. The objective of this research was to identify evidences that would allow describing the importance attached by Accounting professionals to the contents of Management Accounting taught by Accounting courses in Minas Gerais State, Brazil.For this purpose, this study of descriptive and quantitative approach, through documentary analysis of the curriculum frameworks for 39 Higher Education Institution (HEI) from Minas Gerais, identified that 10% of the total hours of undergraduate course is devoted to subjects related to Management Accounting. Through the lesson plans provided by HEI to participants, a ranking was established with 20 curriculum contents more offered to students of Accounting Science related to Management Accounting. These 20 contents were used to prepare a web-surveyquestionnaire sent to all 29,283 counters registered in the Conselho Regional de Contabilidade de Minas Gerais - CRCMG (Regional Accounting Council of Minas Gerais). There were 629 responses. Analyzing the degree of importance attributed by professionals to the contents, we found that in general the average value was greaterthan four, which indicates a degree of importance ranging from "very important" to "extreme importance", ratified by mode, more frequency of grade assigned by the respondents, who also noted the degree four for the contents, confirming the recognition of "great importance" for all them. It was also verified the importance degree attributed by respondent profile. The mode and the mean previously found were confirmed without statistically significant differences among perceptions ofrespondent groups, which shows there is a consensus on the importance of the curriculum contents taught in Accounting Science aimed to Management Accounting. After identifying its relevance according to professional experience of respondents, such contents were verified whether they were sufficient for the learner actingprofessionally with Management Accounting. We obtained 366 negative responses (58%) and 263 positive (42%). By responses analyzed separately according to respondents profile, there were two extremes, one composed by respondents identified as master Teachers, the most optimistic among all the others, indicating 56% of positive responses; on the other hand, 64% of negative answers were identified as people with professional activities related to controlling. Finally, regarding to capability of professional performance and to this research results, this study shows the need to expand the hours devoted to subjects related toManagement Accounting, thereby, to contemplate other contents not yet offered to graduates of Accountancy. Managerial skills of Accounting will only be recognized by the utilization and dissemination of this knowledge to professional counters.